Evaluation of non-volatile metabolites in beer stored at high temperature and utility as an accelerated method to predict flavour stability. (1st June 2016) - Heuberger, Adam L.; Broeckling, Corey D.; Sedin, Dana; Holbrook, Christian; Barr, Lindsay; Kirkpatrick, Kaylyn; Prenni, Jessica E.
Highlights: A high-temperature treatment influenced non-volatile metabolites in beer. Purines varied between 1 and 14 days at 37 °C, including 5-methylthioadenosine (5-MTA). Brewing with modified hops improved flavour stability in an India pale ale. Brewing with modified hops had reduced 5-MTA at regular and high temperature storage. Quantifying 5-MTA at high temperature can predict flavour stability in beer. Abstract: Flavour stability is vital to the brewing industry as beer is often stored for an extended time under variable conditions. Developing an accelerated model to evaluate brewing techniques that affect flavour stability is an important area of research. Here, we performed metabolomics on non-volatile compounds in beer stored at 37 °C between 1 and 14 days for two beer types: an amber ale and an India pale ale. The experiment determined high temperature to influence non-volatile metabolites, including the purine 5-methylthioadenosine (5-MTA). In a second experiment, three brewing techniques were evaluated for improved flavour stability: use of antioxidant crowns, chelation of pro-oxidants, and varying plant content in hops. Sensory analysis determined the hop method was associated with improved flavour stability, and this was consistent with reduced 5-MTA at both regular and high temperature storage. Future studies are warranted to understand the influence of 5-MTA on flavour and aging within different beer types.